Sexual and reproductive health of Syrian refugee adolescent girls: a qualitative study using focus group discussions in an urban setting in Lebanon - Rayan Korri; Sabine Hess; Guenter Froeschl; Olena Ivanova (BMC, 2021)
Plain language summary After almost 10 years of war, Syria's neighboring countries are hosting millions of Syrians who were forcibly displaced. Most prominent among these countries is Lebanon. Adolescent refugee girls are exposed to precarious conditions, which make them more prone to sexual and reproductive health (SRH) problems. This qualitative study was performed in Bourj Hammoud, an urban setting in Lebanon, in order to explore Syrian refugee adolescent girls' SRH perceptions and experiences. The agenda of the International Conference on Population and Development (ICPD) in addition to the Inter-Agency Field Manual on Reproductive Health in Humanitarian Settings (IAFM) and its Adolescent Sexual and Reproductive Health Toolkit for Humanitarian Settings issued by the Inter-Agency Working Group on Reproductive Health in Crises (IAWG) formed the framework of this study. Focus group discussions were performed with 40 Syrian Arab and Syrian Kurdish adolescent girls, each group consisting of five participants aged 13 to 17 years. Different themes were discussed within the groups including menstruation, puberty, and sexual harassment. The participants talked about the social stigma related to menstruation and the social link between puberty, a girl's readiness for marriage, and her need to be careful about sexual harassment. Most of the girls had insufficient information about the female reproductive system. The girls consulted their mothers to learn about SRH issues; however, they expressed a wish to receive well-informed advice from specialists in a safe atmosphere. All the girls reported incidents of sexual harassment, which happened either to them or to other girls they know; however, they were discouraged to report them because they feared other consequences, such as being blamed or not being allowed to go to school anymore. The outcomes of the study show the girls' urgent need to have adequate information about SRH issues and appropriate interventions to prevent sexual and gender-based violence within complex urban settings.